2019
DOI: 10.3390/su11020540
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Adaptive Reuse Practices through User Experiences: Traditional Houses in the Walled City of Nicosia

Abstract: The conservation of traditional residential architecture is crucial in terms of sociocultural continuity. When the traditional houses are no longer used for residential purposes, new functions should be assigned to them for the continuity of the heritage buildings. However, new functions should respect the originality of the heritage building. This research focuses on the conservation and reuse of traditional houses located in the walled city of Nicosia. The walled city is divided into two parts as north and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 26 publications
4
39
0
Order By: Relevance
“…Adaptive re-use of the Haybarn Complex confirmed the assertion made by Mısırlısoy and Günçe [1], that the most appropriate adaptive re-use strategy has a vital importance for heritage building conservation and maintenance of cultural, economic and social values. The authors of this study concluded the same as Mısırlısoy and Günçe [5] that the materials used for restoration should be in harmony with the original materials and in accordance with the structural integrity of the building and space demands of new function activities.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Adaptive re-use of the Haybarn Complex confirmed the assertion made by Mısırlısoy and Günçe [1], that the most appropriate adaptive re-use strategy has a vital importance for heritage building conservation and maintenance of cultural, economic and social values. The authors of this study concluded the same as Mısırlısoy and Günçe [5] that the materials used for restoration should be in harmony with the original materials and in accordance with the structural integrity of the building and space demands of new function activities.…”
Section: Discussionmentioning
confidence: 63%
“…When it comes to interventions, they also need to be carried out without harming the quality impartment and integrity of the building itself. The new function of the restored building must complement its space requirements [5].…”
Section: Introduction and Premisesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the contemporary era, adaptive reuse has been considered as a strategy for protecting these buildings for both present and future generations. At present, the 19th and 20th century conservation and restoration theories are the backbone of the contemporary adaptation movement by introducing different forms of adaptive reuse over time (Günçe & Mısırlısoy, 2019;Yazdani Mehr, 2019).…”
Section: Conceptual Framework: Re-use and Its Importance For İstanbulmentioning
confidence: 99%
“…Nevertheless, there are also some authors claiming that adaptive reuse strategies should be created to use traditional houses "with their original functions or appropriate functions with the authenticity of the original function" [20] (p. 12). This approach is not well suited for the contemporary tendencies shown above that combine adaptive reuse with the new compatible uses.…”
Section: Introductionmentioning
confidence: 99%